1992
DOI: 10.1159/000470355
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Findings in Familial Amyloidotic Polyneuropathy

Abstract: The electrocardiographic findings in patients with verified familial amyloidotic polyneuropathy, from a defined population in northern Sweden with an extremely high prevalence of this disease, were studied. The first electrocardiogram registered, after the diagnosis has been established, was reviewed in 105 patients. In 61 patients, there was at least 1 additional electrocardiogram registered more than 3 years after the first, and the latest of these were also reviewed. Mean follow-up time was 8.2 years. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
(16 reference statements)
3
7
0
Order By: Relevance
“…The only published longitudinal study of ECG changes in FAP patients showed that during a mean follow-up time of 8 years, the prevalence and severity of the conduction disturbances markedly increased and that 19 of 61 (31%) patients required pacemaker treatment during the observation period (18). This is comparable with 4 of 17 (24%) patients in this study over a 5-year period.…”
Section: Long-term Follow-up (N‫)71؍‬supporting
confidence: 74%
See 1 more Smart Citation
“…The only published longitudinal study of ECG changes in FAP patients showed that during a mean follow-up time of 8 years, the prevalence and severity of the conduction disturbances markedly increased and that 19 of 61 (31%) patients required pacemaker treatment during the observation period (18). This is comparable with 4 of 17 (24%) patients in this study over a 5-year period.…”
Section: Long-term Follow-up (N‫)71؍‬supporting
confidence: 74%
“…There are also recent reports of a rapidly progressing cardiomyopathy after liver transplantation for certain TTR mutations (15)(16)(17). An increased prevalence and severity of cardiac arrhythmias and conduction disturbances are the main heart complications in FAP ATTR Val30Met, and the natural course of the disease often leads to the insertion of a pacemaker (18). Cardiac failure is very seldom observed in FAP ATTR Val30Met patients, and none of our patients receiving transplants have developed symptoms consistent with heart failure (19).…”
mentioning
confidence: 61%
“…107,108 Different cross-sectional studies, mainly based on conventional electrocardiograms (ECGs), have revealed a high prevalence of conduction disturbances, intermittent atrial and ventricular arrhythmias, and signs of low voltages in the ECGs. [109][110][111][112] Development of severe arrhythmia is common in V30M patients. A longitudinal study of 12-lead ECG changes in non-transplant ATTR patients over a mean follow-up period of 8 years showed that 19 (31%) of 61 patients required pacemaker implantation during the observation period.…”
Section: Rhythm Disturbancesmentioning
confidence: 99%
“…Pacemaker treatment is frequently used, and with wider indication, as autonomic dysfunction increases the risk of life threatening Adams-Stokes attacks. 27,28 Patients with frequent non-sinus beats also exhibited BP overshoot after tilt reversal. Although this finding may be related to their arrhythmia, we cannot exclude that these patients also had an abnormal cardiac autonomic regulation, but the latter could not be detected as their heart arrhythmia prevented HRV analysis.…”
Section: Discussionmentioning
confidence: 99%